Inheritance of giant mutant plant type in fenugreek (Trigonella foenum-graecum L.) - D L Singhania, R S Raje, D Singh (Journal of Spices and Aromatic Crops, 2002)
The inheritance of giant mutant plant type was worked out by evaluating F1, F2 and Fa generations in a cross (RMt-1 x Mutant) of fenugreek. On the basis of plant type in F1 and the segregation ratios in F2 and F3, it was concluded that the normal plant type of RMt-1 was controlled by a single dominant gene and mutant plant type by its recessive allele.